European Pandemic Recovery: An Opportunity to Reboot - Agnès Bénassy-Quéré; Beatrice Weder di Mauro (Intereconomics)
Abstract Europe’s failure to manage a bold, common response would further increase divergence, strengthen anti-European forces and fuel populism.